Effect of nurses' perception to workplace civility climate on nurse-physician collaboration - Eman Kamel Hossny; Hanaa Esmail Sabra (Wiley, 2021)
Abstract Aims To assess the effect of nurses' perception to workplace civility climate on nurse-physician collaboration and determine whether the largest contributor to changing the climate of the workplace are the employees or top management. Design This study used non‐experimental descriptive cross‐sectional study design, which using purposive sample (139 nurses) working at Health Insurance Hospital. Method The current study data were collected by using self‐administered questionnaires including three tools: (a) a structured interview questionnaire includes personal data; (b) perceived workplace civility climate scale (15 items); and (c) Nurse Physician Collaboration Scale (27 items). Results Main result of this study reveals that there was a positive statistically significant correlation between workplace civility climate and collaboration (0.208*). Studied nurses were perceived top management with the high score (87.5) than employees (65.2). Conclusion Workplace civility climate was demanded for well collaboration between nurses and physicians to provide high‐quality services; when nurses and physicians have increase chance to work in civility climate, combining with response to incivility and low intolerance for it, they will be more collaborated. Recommendation: Policies and procedures are very important in healthcare settings to address uncivil actions and establish a civilized climate.